Animation Deformity: Evaluating the Role of Morphotopologic Features in Suggesting Preventive Surgical Procedures. Issue 6 (15th September 2022) - Onishi, Fumio; Suzuki, Ayumi; Yamakawa, Tomomi; Makino, Jun; Minabe, Toshiharu
Abstract : Background: Animation deformity is an undesirable complication after subpectoral implant reconstruction and is defined as skin distortion during activation of the pectoralis major muscle. However, detailed anatomical features of deformities have yet to be clarified. This study aimed to elucidate how (morphology) and where (topology) animation deformity occurs in reconstructed breasts, and to assess causes and prevention of animation deformity. Methods: This study included 100 consecutive patients with breast cancer, who underwent unilateral subpectoral implant reconstruction. Animation deformity was evaluated, and the patients were grouped according to both morphologic and topologic features. Univariate and multivariate analyses were performed to identify independent factors associated with deformities. Results: The patients were divided into three groups based on skin distortions with or without implant movement: group I, 60 patients with upper-medial dimpling; group II, 41 patients with upper-lateral folding; and group III, 52 patients with mid-lower lines. Overall, 86 patients (86 percent) showed one or more types of deformity. Among the patients with animation deformity, 24 (28 percent) had implant movement. The authors' study identified axillary dissection as an independent factor for the upper-lateral folding group (OR, 0.30), implant volume for the mid-lower lines group (OR, 1.01), and age for implant movement (OR, 1.06). Conclusions: Animation deformity was commonly observed in the cohort of patients who underwent subpectoral implant reconstruction and exhibited three morphotopologic patterns of deformity. The current study demonstrated that the morphotopologic grouping of animation deformity may assist in suggesting possible causes and preventive surgical procedures for these deformities. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.